Long-term outcomes of single-ventricle palliation for pulmonary atresia with intact ventricular septum: Fontan survivors remain at risk of late myocardial ischaemia and death. (12th February 2018) - Elias, Patrick; Poh, Chin Leng; du Plessis, Karin; Zannino, Diana; Rice, Kathryn; Radford, Dorothy J; Bullock, Andrew; Wheaton, Gavin R; Celermajer, David S; d'Udekem, Yves
Abstract: OBJECTIVES: The specific outcomes of patients with pulmonary atresia with intact ventricular septum late after Fontan palliation are unknown. Patients with smaller right ventricles and myocardial sinusoids are known to have worse survival in the first years of life. Whether the potential for coronary ischaemia affects the long-term outcomes of these patients after Fontan palliation is still unknown. METHODS: All patients with pulmonary atresia with intact ventricular septum who underwent the Fontan procedure from 1984 to 2016 in Australia and New Zealand were identified, and preoperative, perioperative and follow-up data were collected. RESULTS: Late follow-up data were available for 120 patients. The median length of follow-up after the Fontan procedure was 9.1 years (interquartile range 4.2–15.4 years). Late death occurred in 9% of patients (11/120). Six were sudden, unexpected deaths; 4 of those occurred in patients known to have right ventricle-dependent coronary circulation (RVDCC). Those with RVDCC had a higher incidence of sudden death (4/20 vs 2/100; P  = 0.007). RVDCC was associated with late death ( P  = 0.01) and the development of myocardial ischaemia after Fontan completion ( P  < 0.001). The 10-year survival rate was 77% (95% confidence interval 56–100%) for patients with RVDCC vs 96% (95% confidence interval 92–100%) for patients without RVDCC. CONCLUSIONS: Long-term survival of patients with pulmonary atresia with intact ventricular septum after the Fontan procedure is excellent, but patients with RVDCC remain susceptible to coronary ischaemia and sudden death. Closer surveillance and investigation for exercise-induced ischaemia may be necessary.